Premorbid Social Functioning and Affective Symptoms Predict Subjective Outcome Among Outpatients With Schizophrenia - Hoertnagl, Christine M.; Kaufmann, Alexandra; Yalcin-Siedentopf, Nursen; Pfaffenberger, Nicole M.; Frajo-Apor, Beatrice; Pardeller, Silvia; Kemmler, Georg; Hofer, Alex (Frontiers in Psychiatry, 2020)
Improving the subjective outcome of patients is an important target in the treatment of schizophrenia. Accordingly, the aim of the present study was to examine the association of factors deemed relevant in this context, i.e. premorbid functioning, residual symptoms, and side effects of antipsychotic medication, with subjective outcome. To this end, 70 clinically stable outpatients with schizophrenia were included into a cross-sectional study. Premorbid functioning, psychopathology, and side effects were assessed by using the Premorbid Adjustment Scale, the Positive and Negative Syndrome Scale, and the Udvalg for Kliniske Undersogelser Side Effect Rating Scale, respectively. Subjective outcome was measured in terms of life satisfaction (Life Satisfaction Questionnaire), self-esteem (Index of Self-Esteem), and needs for care (Berliner Bedürfnisinventar). Both premorbid social functioning and affective symptoms predicted life satisfaction, self-esteem, and patients’ basic needs, whereas positive and negative symptoms predicted needs in the health, social, and functional domains. Concerning side effects, parkinsonism and akathisia showed a significant negative correlation with self-esteem. These findings highlight the complex nature of subjective outcome in patients suffering from schizophrenia. Evidently, premorbid social functioning plays a prominent role in the experienced subjective outcome during the course of the illness. Furthermore, our findings underscore that constant efforts are essential to treat residual symptoms of the disorder and to avoid extrapyramidal motor side effects of antipsychotic medication.